Characterization of corrosion properties, structure and chemistry of titanium-implanted TiNi shape memory alloy; Materials Characterization; Vol. 206 - Semin V. O. Viktor Olegovich; D'yachenko F. A. Filipp Anatoljevich; Erkovich A. V. Alina Vadimovna; Ostapenko M. G. Marina Gennadjevna; Chernova A. P. Anna Pavlovna; Shulepov I. A. Ivan Anisimovich; Savkin K. P. Konstantin Petrovich; Khabibova E. D. Evgeniya Denisovna; Yuzhakova S. I. Sofjya Igorevna; Meysner L. L. Lyudmila Leonidovna (2023, 2023)
Title screen